Economic Feasibility of Anaerobic Digestion To Produce Electricity on Florida Dairy Farms - Russ Giesy; Ann C. Wilkie; Albert De Vries; Roger A. Nordstedt (EDIS)
This paper focuses on the economic feasibilities of using two digester designs suitable for Florida -- covered lagoons and fixed-film digesters to generate electricity for on-farm use or sales.